Pili nut, Canarium ovatum Engl. - Coronel, R.E.; Leibniz Institute of Plant Genetics and Crop Plant Research (1996)
Canarium ovatum (known locally as pili and pilaui) is the most important nut-producing species in the Philippines. Although one of the more typhoon-resistant species, severe typhoons have led to significant destruction of pili trees. The most severe threat is posed by humans who have felled pili trees to sell as lumber or fuelwood in periods of food insecurity following a major typhoon. Collecting missions are needed to sample the remaining diversity. This monograph describes, in a series of 15 chapters, the genetic resources of pili and reviews various aspects of its taxonomy and nomenclature, botany, reproduction, origin, properties, uses, evaluation, breeding, production, ecology, agronomy and limitations, prospects and research needs. Two appendices list (1) Canarium species and their worldwide distribution, and (2) researchers working on pili in the Philippines with information on their contact addresses and area of expertise. (Abstract © CAB ABSTRACTS, CAB International)